Coincidence and common fixed point theorems for four mappings satisfying (alpha(s),F)-contraction - Nazam, Muhammad; Arshad, Muhammad; Postolache, Mihai (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, we manifest some coincidence and common fixed point theorems for four self-mappings satisfying Círíc-type and Hardy–Rogers-type (αs,F)-contractions defined on an αs-complete b-metric space. We apply these results to infer several new and old corresponding results in ordered b-metric spaces and graphic b-metric spaces. Our work generalizes several recent results existing in the literature. We present examples to validate our results. We discuss an application of main result to show the existence of common solution of the system of Volterra type integral equations.
Keywords: fixed point; four mappings; (alpha(s),F)-contraction; alpha(s)-complete b-metric space